Unleashing Growth and Strengthening Resilience in the Caribbean - Srinivasan, Krishna; Alleyne, Trevor; Otker, Inci.; Ramakrishnan, Uma. (Washington, D.C. : International Monetary Fund, 2017)
This book provides a diagnosis of the central economic and financial challenges facing Caribbean policymakers and offers broad policy recommendations for promoting a sustained and inclusive increase in economic well-being. The analysis highlights the need for Caribbean economies to make a concerted effort to break the feedback loops between weak macroeconomic fundamentals, notably pertaining to fiscal positions and financial sector strains, and structural impediments, such as high electricity costs, limited financial deepening, violent crime, and brain drain, which have depressed private investment and growth. A recurring theme in the book is the need for greater regional coordination in finding solutions to address the Caribbean's shared and intertwined macroeconomic and structural challenges. The analysis suggests that strengthening regional and global market integration of Caribbean economies would provide an impetus to sustained growth in incomes and jobs. Greater regional and global economic integration would also facilitate structural transformation and a shift toward new economic activities, resulting in more diversified and less vulnerable economies. A central challenge for the Caribbean is thus to come together as a region, overcome the limitations posed by size, and garner the benefits of globalization. Efforts should build on existing regional arrangements; accelerating progress in implementing these agreements would stimulate trade. Policymakers could also promote deeper integration with Latin America and the rest of the world by pursuing new trade agreements, leveraging current agreements more effectively, or deepening them to include areas beyond traditional trade issues, and developing port and transport infrastructure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet